FACTORS OF BUDGETARY FUNDING FOR HIGHER EDUCATION IN THE EUROPEAN COUNTRIES IN THE CONTEXT OF SUSTAINABLE AND HUMAN DEVELOPMENT: EXPERIENCE FOR UKRAINE - Marianna Kichurchak (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The experience of the EU countries in the formation of the general government expenditures on tertiary education in order to adapt it to the social and economic conditions of Ukraine has been investigated. The purpose of the article is to find out the peculiarities and basic regularities of governmental funding for tertiary education in the EU countries in view of sustainable and human development and to define prospects for improving budgetary support for this sector in the economy of Ukraine. Such scientific methods as induction, deduction, comparison and econometric modelling have been applied. The author has worked out the scientific and methodological approach to identifying factors influencing the governmental financing of tertiary education in the EU countries for sustainable and human development: to carry out a comparative analysis of the dynamics of key indicators of the general government expenditures on tertiary education and evaluate their variation; to determine the main factors which influence the general government expenditures on tertiary education by means of multiple econometric modelling. The following public financing features of higher education in the EU countries are specified: the tendency to increase the volume of the general government expenditures on tertiary education per capita; changing in their structure; their sustainability by GDP. The analysis of the variation indicators has showed the existence of a significant level of differentiation inthe general government expenditures on tertiary education per capita in these countries and relative homogeneity for other indicators (general government expenditures on tertiary education (% of GDP and% of the general government expenditures), their growth rates (% of the previous year). Based on the multiple econometric models, it is determined that GDP at market prices, the total annual net earnings of a single person without children, the situation in the labour market for people with tertiary education, the number of students enrolled in tertiary education (on bachelor’s or equivalent level and at public education institutions) influenced the budgetary funding of higher education in the EU countries. Taking into account the experience of the EU countries, the author has substantiated that in Ukraine, upgrading the government funding of tertiary education for the sustainable and human development is associated with macroeconomic stability, improving the material well-being of individuals and a decrease in unemployment.